Ciudadanía multicultural e interculturalidad - Arista Zerga, Adriana (2006)
The concept of citizenship is going through a conceptual and factual crisis, mainly because of the irruption of minorities of all types, wether in the local or international scenarios. The multiculturalism and the interculturality, in different forms and moments, united with other models of theoretical development can help to get an understanging of the new phenomena and social conflicts appearing at the present time.